A study on Malaysian language learners’ perception towards learning Arabic via online games - Sahrir, Muhammad Sabri; Alias, Nor Aziah (Perbit Universiti Kebangsaan Malaysia, 2011)
This paper reports a study on the perceptions of learning via online games among Arabic elementary language learners at the Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). The survey was a part of a front-end analysis for the design and development of an online Arabic vocabulary games prototype. It elicited learners’ attitude towards Arabic language learning, their attitude towards playing ordinary video games and perceptions of utilizing online games in Arabic language learning. The descriptive quantitative and open-ended survey was distributed among 113 out of 133 learners, taking Arabic language course in an academic semester. The results showed positive level of pre-acceptance among learners’ support and value-addedness of online games were also pronounced in the suggestions put forward by the participants. Based on the findings, the initial design principles were established to guide the development of the online game prototype. The paper further explains how the front end analysis aided the design and development of the online games prototype and ascertained it as a viable application in learning Arabic.